Segmentation Analysis of Staycationers in Jakarta - Oka Suryawardani, I Gusti Ayu; Wardhani, Shinta; Wiranatha, Agung Suryawan (Faculty of Economics and Business Udayana University, 2024)
Staycation has been growing and continuously gaining popularity in Indonesia during and after the COVID-19 pandemic. This study aims to identify segments of staycation tourists/staycationers in Jakarta, one of Indonesia's most popular staycation destinations. Using quantitative methods, this study implements a proportional sampling design based on accommodation types with a total of 130 valid and reliable online questionnaire surveys. This study identifies factors and clusters using lifestyle variables from Activity, Interest, and Opinion (AIO) Model and examines their correlation with demographic, geographic, and behaviour segmentation. Data were analysed by descriptive statistics, including factor analysis, cluster analysis, discriminant analysis, and cross-tabulation analysis. The findings revealed four types of staycationers in Jakarta: (1) I-want-everything staycationers, (2) independent and attention seekers, (3) indulgent shopaholics, and (4) culture and local adventurers. Profiles and characters of each staycationer segment were analysed, giving significant knowledge about staycation market, particularly in Jakarta. Thus, this study offers valuable information for tourism and hospitality businesses to focus on the most potential market segment.